Agglomeration problems and suggested solutions in Veresegyház and Erdőkertes - Balogh, Géza Attila; Péli, László; Ritter, Krisztián (Studia Mundi – Economica, 2020)
In my essay, we examine the situation of Veresegyház and Erdőkertes municipality in regard of newly surfaced problems and social effects due to population growth and development. We carried out a survey on the topic, which was completed by more than 800 citizens. The aim of the survey was to assess the opinion of the public on transportation, public service, businesses, entertainment and to reveal the difficulties they face on a daily basis and how they wish to resolve them on local and regional level as well. The responses indicated that transportation is a key issue at both administration areas: in Veresegyház, the frequent traffic congestions, in Erdőkertes, insufficient road infrastructure seems to be the core of the problem. Furthermore, the overpopulated educational institutions in Veresegyház and the few shopping possibilities in Erdőkertes raised concerns. Residents of Veresegyház give priority to health over infrastructure in regard of local developments. In Erdőkertes, residents prioritize the nursery-matter, public security and establishment of new local businesses. In the matter of regional developments, building out a bypass road that would reduce the dependence on the main roads, and the extension of Misszió Health Center are clearly principal demands. However, it is questionable whether the bypass road could really ease the main road traffic, and the extension and development of Misszió Health Center is relevant. In our opinion, it is worth following the further growth of Erdőkertes and Veresegyház in the long term, considering their ability to retain population, and the possible “counter-urbanisation” processes.